Spatiotemporal analytics - Lee, Jay, 1959- (Boca Raton : CRC Press, 2023)
'This book introduces readers to spatiotemporal analytics that are extended from spatial statistics. Spatiotemporal analytics help analysts to quantitatively recognize and evaluate the spatial patterns and their temporal trends of a set of geographic events or objects, which is important in geography, environmental sciences, economy, and many other domains. This book explains in simple terms the concepts of spatiotemporal data and statistics, theories, and methods used. Each chapter introduces a case study as an example application for an in-depth learning process. The software used and the codes provided enable readers to learn statistics and use them effectively in their projects'--
Introduction to spatiotemporal analytics / Jay Lee -- Spatiotemporal centrography and dispersion / Lang Xue Dang, Huiyu Lin and Jay Lee -- Spatiotemporal quadrat analytics / Zhuo Chen -- Spatiotemporal nearest neighbor analytics / Qingsong Liu and Jay Lee -- Spatiotemporal Ripley's K and L functions / Jay Lee -- Spatiotemporal autocorrelation analytics / Shengwen Li, Xuyang Cheng, Bo Wan, Junfang Gong and Jay Lee -- Spatiotemporal G statistical analytics / Zhuo Chen and Huiyu Lin -- Spatiotemporal Kernel density estimation / Junfang Gong, Zhuang Zeng, Bo Wan, Shengwen Li, and Jay Lee -- Spatiotemporally weighted regression / Bo Huang and Sensen Wu -- Spatiotemporal Bayesian regression / Ortis Yankey, Tao Hu, Han Yue, Peixiao Wang, and Xiao Xu -- Spatiotemporal process analytics and simulations / Moira O'Neill and Jay Lee -- Spatiotemporal analytical unit problems / Lang Xue Dang, Huiyu Lin and Jay Lee.
OCLC-licensed vendor bibliographic record.
Keywords: Spatial analysis (Statistics); Geographic information systems